PP.22.01: RIGHT VENTRICULAR DIASTOLIC DYSFUNCTION IN HYPERTENSIVE PATIENTS. (June 2015) - Zacharopoulou, I.; Tsoukas, A.; Kallistratos, M.S.; Poulimenos, L.E.; Kouremenos, N.; Karamanou, A.; Chamodraka, E.; Vrakas, S.; Kontogianis, N.; Martineos, A.; Tsoukanas, K.; Pagoni, S.; et al.
Abstract : Objective: Diastolic dysfunction (DD) of left ventricle is common in patients with arterial hypertension and reflects changes in ventricular elasticity due to changes in its geometry and structure. Impairment of isovolumetric ventricular relaxation and decreased compliance of the left ventricle are characteristic. DD of the left ventricle is routinely assessed in hypertensive patients however little is known regarding the coexistence of right ventricular DD. We sought to assess right ventricular longitudinal function in hypertensive patients by pulse tissue doppler. Design and method: We prospectively studied 83 subjects (37 hypertensive patients and 46 healthy control subjects) aged 53.4 ± 15.6 years, with preserved EF and sinus rhythm. In both patients and controls a standard Doppler and tissue Doppler echocardiography was performed. Echocardiographic measurements were analyzed by two experienced doctors, being the average of five cardiac cycles, in order to minimize differences during breathing cycle. Exclusion criteria were: valvular heart disease, heart failure with reduced EF, wall motion abnormalities, atrial fibtillation, pulmonary arterial hypertension or lung disease. Results: Hypertensive patients showed impaired right ventricular diastolic indices compared to healthy subjects. At the level of right ventricular lateral tricuspid annulus, hypertensive patients showed a reduction of right ventricular E/A ratio (p = 0.004) and prolongation of relaxation time, as well as lower E peak velocity and S peak (p = 0.002 and p < 0.001 respectively), and increased E/E' ratio (p = 0.002), and peak A velocity (p = 0.008) in comparison to healthy subjects. Conclusions: Hypertensive patients with impaired left ventricular diastolic function present also right ventricular diastolic impairment. This association may reflect right ventricular impairment due to left ventricular pressure overload.